Interstices Issue 18: Surface / Pattern a pursuit of material narratives CFP - Tina Engels-Schwarzpaul (Interstices, 2017)
Interstices Journal of Architecture and Related Arts Issue 18: Surface / Pattern a pursuit of material narratives